PELATIHAN PERILAKU PEMBELIAN KONSUMEN DALAM PEMASARAN MEDIA SOSIAL PADA UKM - Rodhiah; Mahanani, Zenita Dian; Rosyada, Maulin Amrina (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2022)
Consumer purchasing behavior is an action that is directly involved in obtaining, consuming and spending products and services through various media including online social media. The use of social media marketing is described as an application, platform, or media that can facilitate communication, collaboration, or information sharing among users in general and direct sales, customer acquisition, and customer retention. The purpose of the activity is to help business owners have a stock of knowledge about the importance of understanding consumer purchasing behavior through social media. The partner who became the place of activity was a mute craft creative product business located in Serang, Banten. Based on initial observations through online with zoom meetings, partners do not understand about social media consumer behavior, as a medium for communicating partner products to consumers without large costs. The method offered in the activity is training/socialization on basic understanding of marketing consumer behavior and the use of social media marketing. The output of PKM activities is in the form of publications to journals and IPR.